Monte Carlo analysis of megavoltage x-ray interaction-induced signal and noise in cadmium tungstate detectors for cargo container inspection. (17th November 2016) - Kim, J.; Park, J.; Kim, J.; Kim, D.W.; Yun, S.; Lim, C.H.; Kim, H.K.
Abstract: For the purpose of designing an x-ray detector system for cargo container inspection, we have investigated the energy-absorption signal and noise in CdWO 4 detectors for megavoltage x-ray photons. We describe the signal and noise measures, such as quantum efficiency, average energy absorption, Swank noise factor, and detective quantum efficiency (DQE), in terms of energy moments of absorbed energy distributions (AEDs) in a detector. The AED is determined by using a Monte Carlo simulation. The results show that the signal-related measures increase with detector thickness. However, the improvement of Swank noise factor with increasing thickness is weak, and this energy-absorption noise characteristic dominates the DQE performance. The energy-absorption noise mainly limits the signal-to-noise performance of CdWO 4 detectors operated at megavoltage x-ray beam.